Stabilita a změna osobních hodnot u lidí s různými trajektoriemi životní dráhy: longitudinální studie - Millová, Katarína; Blatný, Marek (Československá psychologie, 2021)
Background. Previous research on the stability of personal values in the context of life transitions has usually focused on the presence of a single transition. However, life transitions in everyday life occur simultaneously with other life transitions. The aim of this longitudinal study was therefore to identify different trajectories of life transitions in young adults and to compare the stability of their personal values. Method. In the first wave of research, participants were 18-33 years old; in the second wave, they were 29-43 years old (N = 632; 392 women). In both waves, they completed Schwartzʼs Portrait Value Questionnaires (PVQ); in the second wave, they completed the Life History Calendar focusing on the presence of entry into life transitions. Results. Latent class analysis revealed two trajectories: Experienced transitions (people who experienced all observed transitions) and Partially experienced transitions (people who experienced only entry into regular employment and part of them entered cohabitation). Differential stability of personal values occurred in both trajectories. The differences in the stability of values found between the individual trajectories were insignificant, except for personal values universalism and tradition. Although before entry into life transitions, personal values were not significant predictors of belonging to a particular trajectory, after their experiencing people with the Experienced transitions trajectory more often reached lower levels of values associated with openness to change.
Keywords: sociální hodnoty; mladý dospělý; dospělí; Adult; Longitudinal Studies; lidé; mužské pohlaví; průzkumy a dotazníky; Social Values; Humans; Female; Surveys and Questionnaires; Male; longitudinální studie; životní změny; Young Adult; ženské pohlaví; Life Change Events